Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2174/1568026043388105
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Molecular Determinants of LPS Inhibition by Proteins and Peptides

Abstract: Lipo-poly-saccharide (LPS) induced Gram-negative sepsis and septic shock remain lethal in up to 60 % of cases, and LPS antagonists that neutralize its endotoxic action are the subject of intensive research. The molecular motifs of specific binding of LPS by antiendotoxin proteins and peptides may lead to an understanding of LPS action at the atomic level and provide clues for the development of new immunomodulatory compounds for use as therapy in the treatment of Gram-negative bacterial sepsis. The interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 0 publications
5
72
0
Order By: Relevance
“…Binding of polymyxins to LPS involves an initial electrostatic interaction of the positively charged diaminobutyric acid (Dab) residues with the negatively charged phosphate groups of lipid A, displacing divalent cations (Ca 2ϩ and Mg 2ϩ ) that bridge adjacent LPS molecules (8)(9)(10). We have previously highlighted the deficiencies of directly amine coupling dansyl groups onto the Dab side chains in semisynthetic preparations of dansyl-PMB (11).…”
mentioning
confidence: 99%
“…Binding of polymyxins to LPS involves an initial electrostatic interaction of the positively charged diaminobutyric acid (Dab) residues with the negatively charged phosphate groups of lipid A, displacing divalent cations (Ca 2ϩ and Mg 2ϩ ) that bridge adjacent LPS molecules (8)(9)(10). We have previously highlighted the deficiencies of directly amine coupling dansyl groups onto the Dab side chains in semisynthetic preparations of dansyl-PMB (11).…”
mentioning
confidence: 99%
“…However, overstimulation of the immune system, induced by excess LPS, may produce an overwhelming amount of cytokines that damage host tissues and organs (40 -42). Therefore, structures and interaction studies of AMPs with LPS are vital to better understand their mechanism of antibacterial activities and to facilitate the development of new antiendotoxic/antibacterial agents (43)(44)(45).…”
mentioning
confidence: 99%
“…Tan et al [114] subcloned the N-terminal fragment (CrFCES) and demonstrated that it binds LPS with high affinity of 10 À12 M. Those small fragments in CrFCES were further subcloned and expressed as recombinant Sushi domains [115]. Subsequently, Wang et al [112] demonstrated that the Sushi 1 and Sushi 3 domains are the major LPS-binding regions [52,116]. Although the LPS-binding sites of Factor C have been discovered, defining the precise amino acid residues in the Sushi domains responsible for interacting with LPS would provide insight into the structure-activity relationship as well as the mechanisms of LPS binding.…”
Section: Deriving Sushi Peptides From Factor Cmentioning
confidence: 99%
“…65,2008 Review Article in alternation with hydrophobic residues, BHB(P)HB (B = basic; H = hydrophobic; P = polar). Thus, two 34-amino acid sequences containing BHB(P)HB residues were found within the Sushi 1 and Sushi 3 domains of Factor C. Interestingly, following such a rational approach, Pristovsek and Kidric [52] have further tested various synthetic peptides containing BHB(P)HB motifs and showed LPS-binding andneutralizing capabilities similar to those of Sushi peptides.…”
Section: Deriving Sushi Peptides From Factor Cmentioning
confidence: 99%